DAMPAK BEBAN TUGAS AKADEMIK YANG TIDAK PROPORSIONAL TERHADAP KESEJAHTERAAN PSIKOLOGIS SISWA - Almaida Rahayu; Agus Lestari (Universitas Haji Sumatera Utara, 2025)
This study aims to find out how the disproportionate workload in schools impacts the psychological well-being of students. The subjective experience of the students was examined through semi-structured interviews with a qualitative phenomenological approach. The results showed that teachers experienced stress, mental fatigue, sleep disturbances, and decreased desire to learn due to excessive workload, strict time constraints, and lack of explanation. In addition, frustration and dissatisfaction with unsatisfactory learning outcomes lead to work delays and plagiarism. Many literature reviews showing a link between academic stress and a decline in students' psychological well-being support this conclusion. Taking into account students' cognitive and emotional abilities, this study confirms the importance of changing the learning system to be more humane and proportionate. To support a healthy and meaningful learning process, educators must work together to create a balanced workload and an empathetic pedagogical approach.